THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, RECEIVABLES TURNOVER AND INVENTORY TURNOVER ON COMPANY VALUE AT PT HERO SUPERMARKET TBK FOR THE PERIOD 2012 - 2021 - Triyanto Triyanto; Aria Aji Priyanto (Sean Institute, 2023)
The purpose of this study was conducted to find out whether there is an effect of Current Ratio, Debt To Equity Ratio, Accounts Receivable Turnover and Inventory Turnover on Company Value at PT Hero Supermarket tbk for the 2012-2021 period. The method used in this study is a quantitative research method using associative methods. The results of this study, partially the effect of Current Ratio on Firm Value produces a tcount value of -0.063 < ttable of 2.571 with a significant level of 0.952 > 0.05 which means that the Current Ratio variable has no significant effect on Firm Value. Partially, the effect of the Debt to Equity Ratio on Firm Value produces a tcount value of 4.052 > ttable of 2.571 with a significant level of 0.010 <0.05 which means that the Debt To Equity Ratio variable has a positive and significant effect on Firm Value. Partially, the effect of Receivable Turnover on Firm Value produces a tcount of 1.827 < ttable of 2.571 with a significant level of 0.127 > 0.05 which means that the Receivable Turnover variable has no significant effect on Firm Value. Partially, the effect of Inventory Turnover on Firm Value produces a tcount value of 1.509 < ttable of 2.571 with a significant level of 0.192 > 0.05 which means that the Inventory Turnover variable has no significant effect on Firm Value. Simultaneously the influence of Current Ratio, Debt to Equity Ratio, Accounts Receivable Turnover and Inventory Turnover on Company Value at PT Hero Supermarket Tbk for the 2012-2021 period resulted in an Fcount value of 22.208 > Ftable of 4.534 with a significance level of 0.002 <0.05 meaning that there is a significant influence simultaneous and significant between Current Ratio, Debt to Equity Ratio, Accounts Receivable Turnover and Inventory Turnover to Company Value at PT Hero Supermarket tbk for the 2012-2021 period.